Reflections on the future of the Left - Coates, David, 1946-2018 (Building progressive alternatives., 2017)
What is the future for progressive politics in advanced capitalism? With its political fortunes so low, how might the Left move forward? These essays from leading left intellectuals - Dean Baker, Fred Block, David Coates, Hilary Wainwright, Colin Crouch, Wolfgang Streeck, Leo Panitch, Sam Gindin and Matthew Watson - reflect on the scale and nature of the task that the Left now faces and consider the following questions: (1) What in modern capitalism has brought the Left to this impasse?; (2) What role has the Left played in its own failings?; (3) What lessons can be learnt for progressive politics going forward?; and (4) What are the immediate options and how can they best be pursued? The views and opinions expressed vary, but all offer searching insights into the task the Left now faces. All point to the intellectual and practical experience on which the Left now needs to draw as it deals with its contemporary challenges. These essays represent a major statement on the future for centre-left politics and offer a frank appraisal of the Left's current capacity to keep conservatism at bay and to strengthen radical politics again.